(untitled) (Research, Society and Development, 2021)
Emotional Education applied in the educational context aims to develop self-knowledge about emotions, seeking to improve the quality of life of both the educator and the student. Thus, this study aimed to analyze the influence of ‘Course 101 - Introduction to Transactional Analysis (AT)’ in the understanding, listening and expression of emotions in teachers of an institution of technical and higher courses in southern Brazil. Theoretically, the study is based on authors such as Berne, Steiner, Erskine, among others. Defined as an evaluative research supported by the quantitative methodology, the study counted on the participation of 20 professors from this institution. For data collection, the Emotional Awareness Questionnaire (Steiner and Perry, 1997) was used, applied as a pre-test and post-test. The result of the research demonstrates, through the Wilcoxon T Test, the expansion of the level of ’Emotional Awareness’, specifically with regard to the expansion of the levels of ’Empathy’ and ’Interactivity’.